Horizontal Alveolar Ridge Augmentation with Allogeneic Bone Block Graft Compared with Autogenous Bone Block Graft: a Systematic Review - Thomas Starch-Jensen; Daniel Deluiz; Eduardo Muniz Barretto Tinoco (Stilus Optimus, 2020)
Objectives: The objective of the present systematic review was to test the hypothesis of no difference in implant treatment outcome after horizontal ridge augmentation with allogeneic bone block compared with autogenous bone block. Material and Methods: A MEDLINE (PubMed), Embase and Cochrane Library search in combination with a hand-search of relevant journals was conducted including human studies published in English through March 13, 2019. Comparative and non-comparative studies evaluating horizontal ridge augmentation with allogeneic bone block were included. Cochrane risk of bias tool and Newcastle-Ottawa Scale were used to evaluate risk of bias. Results: One comparative study with high quality and 12 non-comparative studies fulfilled the inclusion criteria. Considerable heterogeneity prevented meta-analysis from being performed. The comparative retrospective short-term study demonstrated no significant difference in implant treatment outcome between the two treatment modalities. Non-comparative long-term studies revealed high implant survival, gain in alveolar ridge width and bone regeneration with allogeneic bone block. However, non-comparative studies disclosed high incidence of complications including dehiscence, exposure of allogeneic bone block and partial or total loss of the grafts. Conclusions: There seemed to be no difference in implant treatment outcome after horizontal ridge augmentation with allogeneic bone block compared with autogenous bone block. However, increased risk of complications was frequently reported with allogeneic bone block.